2010
DOI: 10.37652/juaps.2010.43881
|View full text |Cite
|
Sign up to set email alerts
|

Study the effect of Antibiotics on pyocyanin production from Pseudomonas aeruginosa and pyocyanin as Antibiotic against different pathogenic bacteria

Abstract: P. aeruginosa was cultured on nutrient agar containing different antibiotics, the growth and pigment of bacterial colonies were treated. Azithromycin killed the bacteria on low concentration, colonies of P. aeruginosa treated with Ampicillin, Amoxycillin, and Cefixime appeared light green .Cephalexin and Azithromycin led to formation of light green-yellow colonies, while Doxycillin ,and Clindamycin appeared green ,but there was slight change in colonies color.The pigment (pyocyanin) was extracted from the untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Pyocyanin is known for its antibacterial, antifungal activity and biocontrol agent (Sweedan, 2010;Jayaseelan et al, 2014). As pyocyanin pigment is water-soluble, it has also been reported for its application in aquaculture as an effective agent against fungal diseases and the pathogen Vibrio sp.…”
Section: Introductionmentioning
confidence: 99%
“…Pyocyanin is known for its antibacterial, antifungal activity and biocontrol agent (Sweedan, 2010;Jayaseelan et al, 2014). As pyocyanin pigment is water-soluble, it has also been reported for its application in aquaculture as an effective agent against fungal diseases and the pathogen Vibrio sp.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with those obtained by Khadim and Marjani, who suggested that pyocyanin itself may play a direct role in the observed link between antimicrobial susceptibilities and the phenotype [ 38 ]. Furthermore, Sweedan suggested that pyocyanin production was relatively affected by antibiotic challenges [ 39 ]. In addition to the virulence factors produced by P. aeruginosa , it is also characterized by its ability to form biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…It showed bactericidal action against many pathogenic bacteria like Salmonella paratyphi, E. coli, and Klebsiella pneumonia 152 . The pigment showed very effectual activity against organisms like Acinetobacter, S. aureus, E. coli, and Streptococcus pneumonia 160 . Pyocyanin pigment also showed antibacterial action on food spoilage bacteria like L. monocytogenes and B. cereus.…”
Section: Pyocyanin As Antimicrobial Agentmentioning
confidence: 99%